PENGARUH JUMLAH PRODUKSI, HARGA DAN KURS VALUTA ASING TERHADAP VOLUME EKSPOR IKAN KERAPU DI PROVINSI BALI - Widayanti, Ni Komang Ayu Desi; Sutrisna, I Ketut; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Indonesia's natural potential especially in the fisheries sector can be utilized for international trade activities where the natural resources can be used to meet the needs of other countries. Export of fishery products is one of the subsectors that gives the biggest contribution to the total value of Bali's exports. One of the leading fisheries products exported is grouper fish. This study aims to determine the effect of simultaneous and partial production, price and foreign exchange rates on the volume of grouper fish exports in Bali. The data used in this study are quantitative data and secondary data. Data collection is done by non-behavioral observation techniques and processed by multiple linear regression analysis. Based on the results of the analysis shows that the amount of production, price and foreign exchange rates simultaneously have a significant effect on the volume of grouper exports in Bali. Partially, the number of production and price variables partially has a positive effect on the volume of grouper fish exports in Bali while the foreign exchange rate partially negatively affects the volume of grouper fish exports in Bali. keyword : Export Volume, Production Amount, Price and Foreign Exchange. JEL Classification : F26, E23, O15,024